A correlation between morphology and mechanical performance of injected‐molded PE/EVA/clay nanocomposites: Insight into phase miscibility and interfacial phenomena. Issue 45 (8th June 2020) - Hosseiny, Seyed Majid; Jafari, Seyed Hassan; Khonakdar, Hossein Ali; Hemmati, Farkhondeh; Kalaee, Mohammad Reza
Abstract: In this study, the correlations between the mechanical performance and structural properties of injected‐molded polyethylene (PE)/ethylene‐vinyl acetate copolymer (EVA)/nanoclay (NC) nanocomposites are investigated by revisiting the interfacial phenomena and miscibility state of the component pairs. The effects of different parameters including the injection molding temperature, mixing sequence in melt‐compounding process, blend composition, and nanoclay loading are studied. A great complexity arises in the filling and cooling process of the injected‐molded parts owing to the phase behavior of the polyolefin blend, crystallization, and morphological changes. The injection molding temperature positively influences the elastic modulus, tensile strength and impact strength of PE/EVA/NC systems through the improvements in the PE/EVA partial miscibility, mutual solubility, and interfacial interactions of PE/clay and PE/EVA pairs. By applying a two‐step mixing process before the injection molding, more nanoclay stacks with smaller thicknesses and larger clay interlayer spacing are formed. The stronger pinning effect of nanoparticles in the second mixing sequence retards the phase separation phenomenon of PE/EVA blend during the cooling stage. As a result of improved mutual PE/EVA solubility, the elastic modulus and tensile strength decrease and the impact resistance increases in the PE‐rich systems. On the other hand, an opposite trend for these properties is found for the EVA‐rich systems. Abstract :